(untitled) (Revista Ciencia Agraria, 2025)
The objective was to evaluate the effect of using corn germ and the forage cactus cv. Miúda in the diet of sheep on nutrient intake and digestibility. Four male sheep with an average initial weight of 35 kg, were used, and distributed in a Latin square experimental design. The treatments consisted of four experimental diets: without Miúda cactus (MFC) and germ (CONT); without MFC + germ (GIMEX); with MFC and without germ (MFC); with MFC and germ (MFC+GIMEX). However, a significant effect (P<0.05) of the treatments (T) was observed for the variables of dry matter intake (DMI) (955 x 1304.9 g day-1), mineral matter intake (MMI) (58.7 x 122.1 g day-1), crude protein intake (CPI) (119.9 x 162.9 g day-1) and ether extract intake (EEI) (36.7 x 77.8 g day-1). The diet (GIMEX+MFC) promoted higher DMI and other constituents, while the diet (GIMEX) resulted in lower DMI, MMI and CPI, but favored higher EE intake compared to the diet (GIMEX+MFC). The nutrient digestibility coefficients were not influenced by the association of MFC with corn germ (P>0.05); however, significant effects were observed for the coefficients of digestibility of organic matter (OM) (664.5 x 742.7 g kg-1 DM) and NFC (657.1 x 838.8 g kg-1 DM). The present study determined that combining corn germ with forage palm is a viable option for sheep production in northeastern Brazil in terms of diet quality and utilization.